2019
DOI: 10.3390/molecules24234402
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Induced One-Electron Oxidation of 2-Thiouracil in Aqueous Solutions

Abstract: Oxidative damage to 2-thiouracil (2-TU) by hydroxyl (•OH) and azide (●N3) radicals produces various primary reactive intermediates. Their optical absorption spectra and kinetic characteristics were studied by pulse radiolysis with UV-vis spectrophotometric and conductivity detection and by time-dependent density functional theory (TD-DFT) method. The transient absorption spectra recorded in the reactions of •OH with 2-TU depend on the concentration of 2-TU, however, only slightly on pH. At low concentrations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(25 citation statements)
references
References 106 publications
(146 reference statements)
2
22
1
Order By: Relevance
“…Taking into account, reported in our earlier work, the effect of 2-thiouracil (2-TU) concentration on the transient absorption spectra [ 46 ], we decided to record UV-vis transient absorption spectra at various 2-SeU concentrations to check whether and to what extent concentration of 2-SeU affects spectral characteristics. The spectral changes observed after pulse irradiation of N 2 O-saturated unbuffered aqueous solutions at two pHs (4 and 10) containing 2-SeU in the concentration range of 0.05 mM to 1 mM are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taking into account, reported in our earlier work, the effect of 2-thiouracil (2-TU) concentration on the transient absorption spectra [ 46 ], we decided to record UV-vis transient absorption spectra at various 2-SeU concentrations to check whether and to what extent concentration of 2-SeU affects spectral characteristics. The spectral changes observed after pulse irradiation of N 2 O-saturated unbuffered aqueous solutions at two pHs (4 and 10) containing 2-SeU in the concentration range of 0.05 mM to 1 mM are shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Based on our earlier work on 2-TU [ 46 ], the transient absorption spectrum with λ max = 440 nm was tentatively assigned to the formation of dimeric radical with 2c-3e selenium-selenium bond. In principle, by analogy to 2-TU, the formation of the ● OH adducts at C5 and C6 positions leading to the respective C-centered radicals can also be expected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The azide radical (N 3 ● ) is one of the most important one-electron oxidants used extensively in radiation chemistry studies involving inorganic [ 1 , 2 , 3 ], and aromatic compounds [ 4 , 5 , 6 , 7 , 8 , 9 ], and also molecules of biological significance [ 10 , 11 , 12 , 13 , 14 , 15 ]. In general, it is assumed that N 3 ● reacts in aqueous solution only by electron transfer [ 4 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other interesting examples of using N 3 ● as one-electron oxidant were the studies involving sulfur-substituted nucleobases (thiobases). It was shown that the reactions of 4-thiouracil (4TU(=S)) [ 32 ], and 2-thiouracil (2TU(=S)) [ 15 ] with N 3 ● led to the respective dimeric 2c-3e S-S-bonded radicals in their cationic and neutral forms, respectively (Equations (4) and (5)). N 3 ● + 4TU(=S) → N 3 − + 4TU + (S ● ) 4TU + (S ● ) + 4TU(=S) ⇆ (4TUS∴S4TU) + N 3 ● + 2TU(=S) → N 3 − + 2TU + (S ● ) 2TU + (S ● ) → 2TUS ● + H + 2TU + (S ● ) + 2TU(=S) ⇆ (2TUS∴S2TU) …”
Section: Introductionmentioning
confidence: 99%